Synergistic cortisol suppression by ketoconazole–osilodrostat combination therapy. (8th December 2021) - Amodru, Vincent; Brue, Thierry; Castinetti, Frederic
Abstract : Summary: Here, we describe a case of a patient presenting with adrenocorticotrophic hormone-independent Cushing's syndrome in a context of primary bilateral macronodular adrenocortical hyperplasia. While initial levels of cortisol were not very high, we could not manage to control hypercortisolism with ketoconazole monotherapy, and could not increase the dose due to side effects. The same result was observed with another steroidogenesis inhibitor, osilodrostat. The patient was finally successfully treated with a well-tolerated synergitic combination of ketoconazole and osilodrostat. We believe this case provides timely and original insights to physicians, who should be aware that this strategy could be considered for any patients with uncontrolled hypercortisolism and delayed or unsuccessful surgery, especially in the context of the COVID-19 pandemic. Learning points: Ketoconazole–osilodrostat combination therapy appears to be a safe, efficient and well-tolerated strategy to supress cortisol levels in Cushing syndrome. Ketoconazole and osilodrostat appear to act in a synergistic manner. This strategy could be considered for any patient with uncontrolled hypercortisolism and delayed or unsuccessful surgery, especially in the context of the COVID-19 pandemic. Considering the current cost of newly-released drugs, such a strategy could lower the financial costs for patients and/or society.